1) 4(x-3)=x+6
2) 4-6(x+2)=3-5x
3) (5x+8)-(8x+14)=9
4) 2,7+3y=9(y-2,1)
5)0,3(8-3y)=3,2-0,8(y-7)
6
4,3/5
72
Mejora
хорошист
152 ответов
45.3 тыс. пользователей, получивших
4(x-3)=x+6
4x-12=x+6
4x-x=6+12
3x=18
x=18:3
x=6
4-6(x+2)=3-5x
4-6x-12=3-5x
-8-6x=3-5x
-6x+5x=3+8
-x=11
x=-11
(5x+8)-(8x+14)=9
5x+8-8x-14=9
-3x-6=9
-3x=6+9
-3x=15
x=- 5
2,7+3y=9(y-2,1)
2.7+3y=9y-18.9
3y-9y=-18.9-2.7
-6y=-21.6
y=3.6
0,3(8-3y)=3,2-0,8(y-7)
2.4-0.9y=3.2-0.8y+5.6
-0.9y+0.8y=8.8-2.4
-0.1y=6.4
y=-64
5,6(1,3x-1,5)=3x+3 1/3
7,28x-8,4=3x+3 1/3
7.28x-3x=3 1/3 + 8.4
4.28x=10/3+8.4|*3
12,84x=10+25,2
x=2 952/1284 = 2 238 / 321
z1-z2= 2+i - (-1+2i) = 2+i +1-2i =3 - i
z1*z2= (2+i)*(-1+2i) =-2-i+4i+2i²= -2-i+4i +2*(-1) = -4+3i
(2+i) (2+i) (2+i)*(2i +1) 4i+2i²+2+i 4i+2*(-1)+2+i
z1:z2= = = = = =
(-1+2i) (2i -1) (2i -1)(2i +1) (2i)²-1² 4(-1) -1
5i
= = - i
-5